GE_GERICHTE A/3456/2023 vom 3. Juli 2024 - GE Cour de justice (2024)
RETRAIT DE PERMIS;EXCÈS DE VITESSE;CONDUITE SANS AUTORISATION;CAS GRAVE;INFRACTION;DURÉE;EXPERTISE | LCR.16c.al1; LCR.16c.al2; LCR.16.al3; LCR.17.al3